2021
DOI: 10.3390/antiox10010085
|View full text |Cite
|
Sign up to set email alerts
|

Proniosomal Gel for Topical Delivery of Rutin: Preparation, Physicochemical Characterization and In Vitro Toxicological Profile Using 3D Reconstructed Human Epidermis Tissue and 2D Cells

Abstract: Rutin (Rut) is a natural flavonol, well-known for its broad-spectrum of therapeutic effects, including antioxidant and antitumoral activities; still, it has a reduced clinical outcome due to its limited solubility in aqueous solutions. To overcome this drawback, this study proposes a novel formulation for rutin as a proniosomal gel for cutaneous applications. The gel was prepared by coacervation phase-separation method and complies with the standard requirements in terms of particle size (140.5 ± 2.56 nm), zet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Our results showed that a 24 h treatment with different concentrations of RUT (1, 5, 10, 25, and 50 µM) induced a dose-dependent cytotoxic effect in both types of human melanoma cells tested—RPMI-7951 and SK-MEL-28 and morphological and nuclear alterations (nuclear fragmentation, membrane blebbing, chromatin condensation, and apoptotic bodies), characteristic signs of apoptosis ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ). These results are similar to the ones described in a study conducted on A375 melanoma cells [ 23 ]. Previous publications also reported the in vitro antitumor and proapoptotic properties of RUT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that a 24 h treatment with different concentrations of RUT (1, 5, 10, 25, and 50 µM) induced a dose-dependent cytotoxic effect in both types of human melanoma cells tested—RPMI-7951 and SK-MEL-28 and morphological and nuclear alterations (nuclear fragmentation, membrane blebbing, chromatin condensation, and apoptotic bodies), characteristic signs of apoptosis ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ). These results are similar to the ones described in a study conducted on A375 melanoma cells [ 23 ]. Previous publications also reported the in vitro antitumor and proapoptotic properties of RUT.…”
Section: Discussionsupporting
confidence: 91%
“…The highest percentages were recorded following the 24 h treatment with RUT 50 µM in both cell lines: RPMI-7951—75.25%; SK-MEL-28—84.19%. Regarding the safety profile of RUT, one of our latest publications reveals that RUT induces no cytotoxicity in normal keratinocytes—the predominant cellular component in human skin [ 41 ], even at high concentrations (50 and 75 µM) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since biocompatibility is mandatory for topical formulations, the impact of Bet- and Lup-loaded oleogels on the viability of HaCaT cells has been assessed. This particular cell line has been selected as an in vitro experimental model for skin healthy cells based on the fact that keratinocytes (i) represent the most dominant cellular component of the multi-layered epidermis [ 62 ]; (ii) stand as defensive shields against external harmful factors (e.g., UV radiation) [ 63 ]; and (iii) play a vital role in epidermal wound healing and renewal through a process known as epithelialization, as well as via exerting immune functions [ 62 , 64 ]. Our viability results indicate a lack of cytotoxicity of Blank OG, Bet OG, and Lup OG and a suitable in vitro biocompatibility on HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Software (Olympus, Tokyo, Japan). Staurosporine solution—5 µM—was used as positive control for apoptosis (3 h at 37 °C) and Triton X-100 (30 min at 37 °C)—0.5% for necrosis [ 62 ].…”
Section: Methodsmentioning
confidence: 99%